Does early skin-to-skin contact have a long-term effect on the emotional and behavioral development of very preterm infants? - Trautmann-Villalba, Patricia; Heine, Eva; Kribs, Angela; Mehler, Katrin (Frontiers in Psychology, 2024)
Premature birth may impair a sensitive, responsive, enjoyable and regulating parenting style and increase the risk for behavioural, cognitive and emotional deficits. In the same way, the establishment of the emotional bond to the infant may be disturbed through the restrictions and difficulties at the Neonatal Intensive Care Unit (NICU), with similar negative effects on children's development. Skin-to-skin contact (SSC) directly after birth is strongly recommended also for preterm or low-birth-weight infants since there is high-certainty evidence that SSC has positive effects on neonatal and maternal health as well as on the quality of the parent-child-relationship. The aim of this study was to examine the effect of skin-to-skin contact immediately after childbirth on the development of emotional and behavioural problems in children born preterm entering school.Methods: This study is part of a randomized controlled delivery room skin-to-skin study (Deisy Study). 33 children (aged 6-8 years) were assessed at school start. The German version of the CBCL/6-18R was used to evaluate the presence of behaviour problems.Results: The perceived parental stress 6 months after discharge was the variable that most contributed to the variance explanation. SSC immediately after childbirth was not significant in the prediction of emotional and behavioural problems at school start.Limitations: Small study group. Partners' variables were not included. Information regarding sociodemographic variables and bonding quality was collected 6 months (corrected age) after birth. The measurement of children's behavioural problems is not objective and corresponds to the parents' perception.